Practical application of business education through administrative fellowship - Schwartzkopf, Joel W., author (Colorado State University. Libraries, 2018)
The CSU Health Network Administrative Fellowship seeks to mirror the model of the approximately 75+ other such programs in the United States. Administrative fellowships are found in many health systems and hospitals, including locally at UCHealth and Children’s Hospital Colorado, and at institutions as well known as Duke, the Mayo Clinic, and Johns Hopkins. Traditionally, an administrative fellowship is completed immediately after the awarding of an MBA or MHA (Master of Healthcare Administration). At CSUHN, we specifically sought to provide a similar experience for a practicing mid-career clinician (physician, PA, or NP) who also held or was near completion of an MBA or MHA. For the inaugural year of the CSUHN fellowship, the incumbent was a senior MBA student at CSU and a full-time PA in the medical clinic. The curriculum of the CSUHN fellowship placed the fellow as a de facto member of the organization’s leadership team for one year, allowing access to the highest levels of decision making and strategic planning. The fellow attended the weekly leadership team meetings and had weekly one-on-one sessions with the Director of Medical Services, who served as the mentor for the fellowship. This high-level exposure gave the fellow the opportunity to become involved in the operations of every part of this large and diverse clinic, applying the knowledge, skills, and abilities learned in the MBA program. The “primary benefit the fellow receives is exposure to senior management— something that cannot be duplicated any other way, both in the depth of senior management and breadth of the organization.”(1)
288 - Joel Schwartzkopf
Creating an administrative fellowship at the CSU Health Network
College of Business; CSU Health Network.
Keywords: administrative; fellowship; MBA; healthcare; medicine; business; provider